2003
DOI: 10.1104/pp.103.024380
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungi Can Dominate Phosphate Supply to Plants Irrespective of Growth Responses

Abstract: Arbuscular mycorrhizal (AM) fungi are vital components of nearly all terrestrial ecosystems, forming mutually beneficial (mutualistic) symbioses with the roots of around 80% of vascular plants and often increasing phosphate (P) uptake and growth. We present novel data showing that AM fungi can provide the dominant route for plant P supply, even when overall growth or P uptake remains unaffected. The results will change our understanding of the roles of AM fungi in agricultural and natural ecosystems; they also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
584
7
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 827 publications
(662 citation statements)
references
References 30 publications
21
584
7
22
Order By: Relevance
“…This implies that the probability of arsenate entering plants directly through the phosphate uptake system may decrease greatly. Taking together the studies by Burleigh (2001) and Smith et al (2003) an interesting relationship between the capacities of AMF to provide P nutrition and downregulate the phosphate transporter can be suggested. Thus, for a particular AMF, the more P nutrition supplied, the more strongly the transcription of the phosphate transporter may be suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the probability of arsenate entering plants directly through the phosphate uptake system may decrease greatly. Taking together the studies by Burleigh (2001) and Smith et al (2003) an interesting relationship between the capacities of AMF to provide P nutrition and downregulate the phosphate transporter can be suggested. Thus, for a particular AMF, the more P nutrition supplied, the more strongly the transcription of the phosphate transporter may be suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies on the kinetics of phosphate/arsenate uptake have suggested that AMF can downregulate phosphate/arsenate transporters in both arsenate resistant and non-resistant Holcus lanatus (Gonzalez-Chavez et al, 2002). Recent studies have established that the mycorrhizal pathway, in contrast with the direct root uptake pathway, can dominate plant P uptake, so that most (perhaps almost all) of the plant P comes from AMF (Smith et al, 2003). This implies that the probability of arsenate entering plants directly through the phosphate uptake system may decrease greatly.…”
Section: Resultsmentioning
confidence: 99%
“…The data indicate that host genetic factors influence fungal growth strategy with an impact on plant performance. with Smith et al (2003). The growth medium (hereafter referred to as soil) was a 1:1 (w:w) mixed into the soil.…”
Section: Resultsmentioning
confidence: 99%
“…However, the compartmented cultivation system used in the present study has obvious advantages (Smith et al, 2003): C B occupied only 5% volume of C A and the system allows investigations on elemental uptake and translocation by mycorrhiza or hyphae under nearly natural conditions without serious interference from spatial restriction of root growth.…”
Section: Discussionmentioning
confidence: 99%